Evaluation of the Effectiveness of Civic Education on Acquisition of Social Cohesion Competency among Secondary School Students in Uasin Gishu County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the evaluation was to establish the effect of civic education on social cohesion in secondary schools in Uasin Gishu county Kenya. The evaluation was guided by the Constructivist theory and (CIPP) model. Causal comparative design was used. Target population included 142 secondary schools, 142 teachers and 8520 students. Stratified and simple random sampling techniques were used to select 256 History and Government students from 43 schools. The study used Questionnaire for data collection. Data collected was analyzed using descriptive and inferential statistics. Descriptive statistics was in form of frequencies, percentage, means and standard deviation. Independent t-test, multiple regression and chi-square were adopted to test the hypotheses. The study established that majority of the students have been taught all the topics in civic education. The assessment methods commonly used to evaluate the teaching of civic education were use of objective tests and oral questions. The findings indicated that majority of the students scored below average on the items that measured the knowledge of the students on the core tenets of civic education. Majority of the students were generally likely to treat others well. The overall mean for the aggression scale was 2.46 in a scale of 0-6 times which implies that majority of the students were likely to do wrong to their colleagues two times. On ethnocentric scale, majority of the students believed that their culture is superior to others. Further, majority of the students were somewhat likely to forgive. Majority of the students feel nervous when they speak in front of a group and they were concerned about what other people think of them. To some extent, the students are self-conscious. The study established that there was a significant relationship between students’ level of knowledge on civic education and the internalization of the core tenets of civic education.